Indonesian English learning preferences - Lisa Ramadhani Harianti; Aji Prasetya Wibawa; Bety Masruroh; Vira Setia Ningrum; Eka Nurcahya Ningsih (Association for Scientific Computing Electrical and Engineering(ASCEE), 2024)
This study examines the language learning preferences of Indonesians by comparing search trends for popular formal English courses and English learning applications using Google Trends data. The data is visualized and analyzed descriptively, revealing Ruang Guru as the most preferred English language institution in Indonesia. Its popularity is attributed to service promotions, user-friendly websites, and efficient marketing techniques. Simultaneously, Grammarly is observed as the most popular English learning application among Indonesian learners, emphasizing the importance of refining writing skills. A comparison of search results between Grammarly and Ruang Guru highlights Grammarly's dominance and the preference for self-directed and flexible learning options among Indonesians. These findings have significant implications for education policymakers, language application developers, and English course institution managers. The study suggests a need for the formulation of courses that align with the preferences of Indonesian learners, facilitating autonomous and flexible learning experiences. This insight can guide strategic decisions to enhance the effectiveness and relevance of English language education in Indonesia.